Laser cladding of nanoparticle TiC ceramic powder: Effects of process parameters on the quality characteristics of the coatings and its prediction model. (August 2019) - Chen, Tao; Wu, Weining; Li, Wenpeng; Liu, Defu
Highlights: PT, SD and LP had the most importance on the coating quality characteristics. Optimal process parameters for the ceramic coatings were identified. Quality characteristics of the ceramic coatings were predicted well by SVM model. Abstract: In laser cladding process, the quality characteristics of the coatings are directly affected by laser cladding process parameters. In this work, in order to investigate the effects of the process parameters on the quality characteristics of the ceramic coatings on Ti6Al4V substrates, which were prepared by laser cladding using nanoparticle TiC powder as pre-placed material, five single factors (laser power, scanning speed, pre-placed powder thickness, laser spot diameter and multi-track overlapping ratio) and four interactions related to laser power were selected as influencing factors, and then multi-track cladding experiments with L 27 (3 13 ) orthogonal array designed by Taguchi method were carried out to obtain the geometric characteristics (coating thickness, coating width and height difference) and mechanical property (micro-hardness) of the coatings. Based on experimental results, the influence extents of all factors on quality characteristics were ranked by signal-to-noise (S/N) ratio, and the significances of all factors on quality characteristics were evaluated by using P -value from the analysis of variance (ANOVA). Then the effects of the significance factors on quality characteristic were analyzed in detail, and the optimal process parameters were selected. Finally, a prediction model based on support vector machine (SVM) was developed for the quality characteristics of the cladding coatings. The results showed that the pre-placed powder thickness, laser spot diameter and laser power were the most crucial process parameters. The prediction model based on SVM method can correctly describe the relations between cladding process parameters (input variables) and quality characteristics of coatings (output characteristics), with the correlation coefficient CC > 0.94. This research work gives a guideline for the selection of appropriate process parameters for laser cladding of high-quality coatings using nanoparticle TiC ceramic powder as starting material.